2022
DOI: 10.1098/rspb.2022.0147
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected morphological diversity in ancient dogs compared to modern relatives

Abstract: Dogs are among the most variable species today, but little is known about the morphological variability in the early phases of their history. The Neolithic transition to farming may have resulted in an early morphological diversification as a result of changes in the anthropic environment or intentional selection on specific morphologies. Here, we describe the variability and modularity in mandible form by comparing 525 dog mandibles from European archaeological sites ranging from 8100 to 3000 cal. BC to a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Modern specimens are often the only available reference of securely identified species, however, it has been demonstrated that modern references can lead to misidentifications. For example, modern dog breeds are not a good proxy to identify archaeological specimens [93]. This is also the case for other domestic species for which it is well known that direct selection over the last two centuries was intensified, followed by standardization of morphology and performance with the emergence of the breed concept [94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Modern specimens are often the only available reference of securely identified species, however, it has been demonstrated that modern references can lead to misidentifications. For example, modern dog breeds are not a good proxy to identify archaeological specimens [93]. This is also the case for other domestic species for which it is well known that direct selection over the last two centuries was intensified, followed by standardization of morphology and performance with the emergence of the breed concept [94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…Could this be the underlying reason why dogs display the fullest number of traits falling under the domestication syndrome in 42 ? In addition, we must bear in mind that the extended period of sociality induced by selective breeding carries with it its own anatomical consequences 46,47 that may in part obscure the impact of the earliest stages of domestication and the presence of the 'domestication syndrome' in its most pristine form, as it were. This point is made particularly clearly in 48 , whose comprehensive phylogenetic analysis of the effect of sociality, insularity, and domestication on brain size demonstrates the robust relationship between domestication and brain size reduction (contra 39 ), but also highlights the confounding effect of extended sociality (often associated with brain size increase).…”
Section: What the Hypothesis Is (Not)mentioning
confidence: 99%
“…With the emergence of agriculture and, more generally speaking, the Neolithic transition, the human niche construction caused a major ecological disturbance, with the opening and fragmentation of the landscape, the emergence and spread of domesticated animals and plants from several independent centres across Eurasia, the protection of livestock from predators and competitors, and the dispersal of invasive species and pathogens (Ellis et al, 2021;Sullivan et al, 2017). To date, the influence of the Neolithic niche construction has been mainly explored through human-induced species distribution (Boivin et al, 2016;Cucchi et al, 2020;Vigne, 1999), and over the temporal depth of the direct human influence over species during the process of animal domestication (Ameen et al, 2019;Brassard et al, 2022;Clutton-Brock, 1992;Cucchi et al, 2021;Fages et al, 2019;Frantz et al, 2020;Larson and Fuller, 2014;Zeder, 2015). Yet, its consequences on non-domestic species evolution remain to be fully documented and understood (Erlandson et al, 2016;Sarrazin and Lecomte, 2016).…”
Section: Introductionmentioning
confidence: 99%